Say pays!: Shareholder voice and firm performance - Vicente Cu\~nat; Mireia Gine; Maria Guadalupe (W.E. Upjohn Institute for Employment Research, 2013)
This paper estimates the effect of increasing shareholder voice in corporations through a new governance rule that provides shareholders with a regular vote on pay: Say on Pay. We apply a regression discontinuity design to Say on Pay shareholder proposals to deal with prior expectations and the endogeneity of internal governance rules. Adopting Say on Pay leads to large increases in market value (5.4 percent), firm profitability, and long-term performance. In contrast, we find small effects on the level and structure of pay. This suggests that Say on Pay operates as a regular confidence vote, increasing efficiency, and market value.
Keywords: G34; D21; G14; 330; Agency Cost; Corporate Governance; Shareholder Meetings; Regression Discontinuity; Event Studies